Self-flame-retardant organic phase change energy storage composite material and preparation process thereof

The self-flame retardant organic phase change energy storage composite material addresses flammability issues by integrating a multi-step synthesized flame retardant with a modified melamine formaldehyde shell, ensuring effective flame retardancy and thermal conductivity.

CN119220041APending Publication Date: 2024-12-31HENAN ACADEMY OF SCI CHEM RES INST CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411493514.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

Existing organic phase change energy storage materials are flammable, posing serious safety hazards in high-temperature environments and increasing the risk of fire accidents.

Method used

A self-flame retardant organic phase change energy storage composite material is prepared by introducing a new flame retardant with a phosphorus-nitrogen structure, synthesized in multiple steps, and incorporating a methanol-modified melamine formaldehyde shell with conductive fillers to enhance flame retardancy and thermal conductivity.

Benefits of technology

The composite material exhibits both solid-phase and gas-phase flame retardancy, effectively preventing combustion and maintaining thermal conductivity, thus enhancing safety and environmental friendliness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119220041A_ABST
    Figure CN119220041A_ABST
Patent Text Reader

Abstract

The invention provides a self-flame-retardant organic phase change energy storage composite material and a preparation process thereof, and belongs to the technical field of preparation of organic phase change energy storage materials. The preparation process comprises the following steps: preparing a novel flame retardant intermediate product; preparing a novel flame retardant; preparing the modified melamine formaldehyde; and preparing the organic phase change energy storage composite material. The microcapsule organic phase change energy storage composite material with a multi-layer structure is prepared, the defect of low thermal conductivity is overcome by taking the methanol modified melamino-formaldehyde as a shell and adding the conductive filler, the prepared organic phase change energy storage composite material has good thermal conductivity and thermal stability, and the novel flame retardant is added, so that the composite material has good thermal conductivity and thermal stability. The organic phase change energy storage composite material has good flame retardant property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of preparation of organic phase change energy storage materials, and in particular to a self-flame retardant organic phase change energy storage composite material and a preparation process thereof. Background Art

[0002] Phase change energy storage materials, as a material that can absorb and release a large amount of latent heat within a specific temperature range, have important application value in the field of energy storage and utilization. At present, organic phase change energy storage materials have attracted much attention due to their advantages such as suitable phase change temperature, large phase change latent heat, and good chemical stability.

[0003] However, existing organic phase change energy storage materials generally have some problems. On the one hand, most organic phase change materials are flammable and pose serious safety hazards during use. For example, in some application scenarios that require high temperature environments or may come into contact with fire sources, once organic phase change materials burn, it will not only cause the energy storage system to fail, but may also cause fire accidents, resulting in huge economic losses and casualties.

[0004] Therefore, we proposed a self-flame retardant organic phase change energy storage composite material and its preparation process, which effectively improved the flame retardant properties of the material and reduced safety risks. Summary of the invention

[0005] In view of the deficiencies in the prior art, the object of the present invention is to provide a self-flame retardant organic phase change energy storage composite material and a preparation process thereof.

[0006] A self-flame retardant organic phase change energy storage composite material and a preparation process thereof, comprising the following steps:

[0007] S1: Preparation of novel flame retardant intermediates

[0008] Phosphorus pentachloride, tetrachloroethane and ammonium sulfate are used as raw materials to react to generate N-dichlorophosphoryl-P-trichloromonophosphazene monomer, which is then reacted again to prepare an intermediate product, polydichlorophosphazene;

[0009] S2: Preparation of new flame retardants

[0010] After multi-step synthesis, a variety of flame retardant functional groups were introduced to prepare a new flame retardant;

[0011] S3: Preparation of modified melamine formaldehyde

[0012] The melamine-formaldehyde prepolymer is modified by methanol to obtain modified melamine formaldehyde;

[0013] S4: Preparation of organic phase change energy storage composite materials

[0014] A reaction solution is prepared by mixing styrene-maleic anhydride copolymer, sodium hydroxide, a new flame retardant and sodium dialkylbenzene sulfonate, dodecanol is added to the reaction solution, and then modified melamine formaldehyde and a mixed solution of boron carbide and carbon nanotubes are added, mixed and reacted to obtain an organic phase change energy storage composite material.

[0015] Furthermore, the preparation of the novel flame retardant intermediate product in step S1 specifically comprises the following steps:

[0016] S1.1: 80-90 parts by weight of phosphorus pentachloride, 220-230 parts by weight of tetrachloroethane and 10-12 parts by weight of ammonium sulfate are mixed uniformly under nitrogen protection, and the temperature is raised to 145-150° C., and the reaction is carried out for 1-2 hours. After the reaction is completed, the reaction is filtered and the reaction is rotary evaporated under reduced pressure to obtain the reaction product, N-dichlorophosphoryl-P-trichloromonophosphazene monomer;

[0017] S1.2: reacting N-dichlorophosphoryl-P-trichloromonophosphazene monomer in a nitrogen atmosphere at 240-250°C for 2-3h. After the reaction is completed, an intermediate product, polydichlorophosphazene, is obtained.

[0018] Furthermore, step S2 of preparing the novel flame retardant specifically comprises the following steps:

[0019] S2.1: 5-8 parts by weight of the intermediate product polydichlorophosphazene is dissolved in 200-230 parts by weight of tetrahydrofuran, and then 2-3 parts by weight of 4-hydroxysodium benzaldehyde is added, and the mixture is reacted at 65-68° C. and nitrogen atmosphere for 6-7 hours. After the reaction is completed, 2-3 parts by weight of sodium phenolate are added, and the mixture is reacted at 70-75° C. for 20-24 hours. After the reaction is completed, the mixture is filtered, washed, and dried to obtain reactant Ⅰ [(NP(OC6H4CHO)(OPh)) 0.4 (POPh2) 0.6 ] n ;

[0020] S2.2: 3-5 parts by weight of reactant I are dissolved in 10-12 parts by weight of a mixed solution of tetrahydrofuran / methanol, and then 2-3 parts by weight of sodium borohydride are added. The mixture is reacted for 23-24 hours under a nitrogen atmosphere. After the reaction, the mixture is washed with hot water and dried to obtain reactant II [(NP(OC6H4CH2OH)(OPh)) 0.4 (POPh2) 0.6 ] n ;

[0021] S2.3: After mixing 2-3 parts by weight of epichlorohydrin and 3-5 parts by weight of reactant II, add 0.1-0.2 parts by weight of catalyst hexadecyltrimethylammonium bromide under a nitrogen atmosphere, stir at 70-75°C for 2-3 hours, then add 2-3 parts by weight of sodium hydroxide solution, react at 85-88°C for 2-3 hours, and after the reaction, perform rotary evaporation, wash, filter and dry to obtain a new flame retardant.

[0022] Furthermore, step S3 of preparing modified melamine formaldehyde specifically comprises the following steps:

[0023] S3.1: 0.1-0.2 parts by weight of hexamethylenetetramine and 50-60 parts by weight of formaldehyde solution are stirred and mixed, and then 10-12 parts by weight of melamine powder are added, and the mixture is heated in a water bath to 80-85° C. for reaction for 1-2 hours, and then triethanolamine is added to adjust the pH value to 9.1-9.3 to obtain a melamine-formaldehyde prepolymer;

[0024] S3.2: Add the above melamine-formaldehyde prepolymer to 60-70 parts by weight of methanol, stir and react for 1-2 hours to obtain modified melamine formaldehyde.

[0025] Furthermore, step S4 of preparing the organic phase change energy storage composite material specifically comprises the following steps:

[0026] S4.1: Add 10-12 parts by weight of styrene-maleic anhydride copolymer to 200-230 parts by weight of deionized water, stir and mix at 50-55° C. for 20-30 minutes, then add sodium hydroxide solution to adjust the pH value to 8-9, stir for 1-2 hours, then add 1-2 parts by weight of a new flame retardant and 0.4-0.5 parts by weight of sodium dialkylbenzene sulfonate to obtain a reaction solution;

[0027] S4.2: Add 7-8 parts by weight of dodecanol to 23-25 ​​parts by weight of the reaction solution, stir and mix at 500-600 r / min, then add 1-2 parts by weight of modified melamine formaldehyde, then stir and react at 70-75°C for 1-2 hours, then add 1-2 parts by weight of a mixed solution of 10wt% boron carbide and carbon nanotubes, react for 1-2 hours, wash and dry after the reaction is cooled to obtain an organic phase change energy storage composite material.

[0028] Furthermore, in step S2.2, the volume ratio of tetrahydrofuran to methanol is 1:1.

[0029] Furthermore, the sodium hydroxide solution in step S2.3 is a 40 wt % sodium hydroxide solution.

[0030] Furthermore, the sodium hydroxide solution in step S4.1 is a 10 wt % sodium hydroxide solution.

[0031] Furthermore, in the mixed solution of step S4.2, the weight ratio of boron carbide to carbon nanotubes is 1:1.

[0032] A self-flame retardant organic phase change energy storage composite material is prepared by any one of the above-mentioned preparation processes for the self-flame retardant organic phase change energy storage composite material.

[0033] Compared with the prior art, the present invention has at least the following beneficial effects:

[0034] 1. The present invention prepares a new flame retardant and adds it to an organic phase change energy storage composite material. The new flame retardant is synthesized in multiple steps and a variety of flame retardant functional groups are introduced. After the new flame retardant is added, the phosphorus and nitrogen content in the organic phase change energy storage composite material increases, and the flame retardancy is enhanced. The phosphorus-nitrogen structure of the new flame retardant has a synergistic flame retardant effect, so that the new flame retardant containing the phosphazene structure has both solid-phase and gas-phase flame retardancy during combustion, so that the solid non-combustible material after combustion can adhere to the surface of the combustion matrix, which has the effect of isolating external oxygen and heat. At the same time, the generated non-combustible gas can take away part of the heat, and can also prevent the diffusion of oxygen in the organic phase change energy storage composite material, effectively hindering the continued combustion of the material, thereby effectively improving the flame retardant properties of the organic phase change energy storage composite material.

[0035] 2. The present invention prepares a multi-layer microcapsule organic phase change energy storage composite material, using methanol-modified melamine formaldehyde as the shell, and adding conductive fillers to solve the defect of low thermal conductivity. The prepared organic phase change energy storage composite material has good thermal conductivity and phase change energy storage capacity. Melamine formaldehyde is modified by methanol to obtain a methylated melamine formaldehyde shell, thereby reducing the free formaldehyde content and reducing the harm to the environment and human health, making the organic phase change energy storage composite material safe and environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] The accompanying drawings, which are incorporated herein and constitute a part of the specification, illustrate embodiments of the present disclosure and, together with the description, further serve to explain the principles of the present disclosure and to enable those skilled in the relevant art to make and use the present disclosure.

[0037] Figure 1 The present invention is a flow chart of a process for preparing a self-flame retardant organic phase change energy storage composite material used in an embodiment of the present invention. DETAILED DESCRIPTION

[0038] The following is a detailed description of the preparation process of a self-flame retardant organic phase change energy storage composite material provided by the present invention in combination with the accompanying drawings and specific embodiments. At the same time, it is explained here that in order to make the embodiments more detailed, the following embodiments are the best and preferred embodiments, and those skilled in the art may also adopt other alternative methods to implement some known technologies; and the accompanying drawings are only for a more specific description of the embodiments, and are not intended to specifically limit the present invention.

[0039] Example 1

[0040] A preparation process of a self-flame retardant organic phase change energy storage composite material, such as Figure 1 As shown, the following steps are included:

[0041] S1: Preparation of novel flame retardant intermediates

[0042] S1.1: 80 parts by weight of phosphorus pentachloride, 220 parts by weight of tetrachloroethane and 10 parts by weight of ammonium sulfate were mixed uniformly under nitrogen protection, and the temperature was raised to 145°C for reaction for 1 hour. After the reaction was completed, the mixture was filtered and rotary evaporated under reduced pressure to obtain the reaction product, N-dichlorophosphoryl-P-trichloromonophosphazene monomer;

[0043] S1.2: reacting N-dichlorophosphoryl-P-trichloromonophosphazene monomer in a nitrogen atmosphere at 240° C. for 2 h, and obtaining an intermediate product, polydichlorophosphazene;

[0044] S2: Preparation of new flame retardants

[0045] S2.1: 5 parts by weight of the intermediate product polydichlorophosphazene are dissolved in 200 parts by weight of tetrahydrofuran, and then 2 parts by weight of 4-hydroxysodium benzaldehyde are added, and the mixture is reacted at 65° C. and nitrogen atmosphere for 6 hours. After the reaction is completed, 2 parts by weight of sodium phenolate are added, and the mixture is reacted at 70° C. for 20 hours. After the reaction is completed, the mixture is filtered, washed, and dried to obtain reactant Ⅰ [(NP(OC6H4CHO)(OPh)) 0.4 (POPh2) 0.6 ] n ;

[0046] S2.2: 3 parts by weight of reactant I was dissolved in 10 parts by weight of a mixed solution of tetrahydrofuran / methanol in a volume ratio of 1:1, and then 2 parts by weight of sodium borohydride was added. The mixture was reacted for 23 hours under a nitrogen atmosphere. After the reaction, it was washed with hot water and dried to obtain reactant II [(NP(OC6H4CH2OH)(OPh)) 0.4 (POPh2) 0.6 ] n ;

[0047] S2.3: After mixing 2 parts by weight of epichlorohydrin and 3 parts by weight of reactant II, 0.1 parts by weight of catalyst hexadecyltrimethylammonium bromide was added under nitrogen atmosphere, stirred at 70°C for 2 hours, then 2 parts by weight of 40wt% sodium hydroxide solution was added, reacted at 85°C for 2 hours, and after the reaction, rotary evaporation, washing, filtering and drying were performed to obtain a novel flame retardant;

[0048] S3: Preparation of modified melamine formaldehyde

[0049] S3.1: 0.1 parts by weight of hexamethylenetetramine and 50 parts by weight of formaldehyde solution are stirred and mixed, and then 10 parts by weight of melamine powder are added, and the mixture is heated to 80° C. in a water bath for reaction for 1 hour, and then triethanolamine is added to adjust the pH value to 9.1 to obtain a melamine-formaldehyde prepolymer;

[0050] S3.2: adding the above melamine-formaldehyde prepolymer to 60 parts by weight of methanol, stirring and mixing for 1 hour to obtain modified melamine formaldehyde;

[0051] S4: Preparation of organic phase change energy storage composites

[0052] S4.1: Add 10 parts by weight of styrene-maleic anhydride copolymer to 200 parts by weight of deionized water, stir and mix at 50° C. for 20 minutes, then add 10 wt% sodium hydroxide solution to adjust the pH value to 8, stir for 1 hour, then add 1 part by weight of a new flame retardant and 0.4 parts by weight of sodium dialkylbenzene sulfonate to obtain a reaction solution;

[0053] S4.2: Add 7 parts by weight of dodecanol to 23 parts by weight of the reaction solution, stir and mix at 500 r / min, then add 1 part by weight of modified melamine formaldehyde, then stir and react at 70°C for 1 hour, then add 1 part by weight of a mixed solution of 10wt% boron carbide and carbon nanotubes in a weight ratio of 1:1, react for 1 hour, wash and dry after the reaction is cooled to obtain an organic phase change energy storage composite material.

[0054] Example 2

[0055] A preparation process of a self-flame retardant organic phase change energy storage composite material, such as Figure 1 As shown, the following steps are included:

[0056] S1: Preparation of novel flame retardant intermediates

[0057] S1.1: 90 parts by weight of phosphorus pentachloride, 230 parts by weight of tetrachloroethane and 12 parts by weight of ammonium sulfate were mixed uniformly under nitrogen protection, and the temperature was raised to 145°C for reaction for 1 hour. After the reaction was completed, the mixture was filtered and rotary evaporated under reduced pressure to obtain the reaction product, N-dichlorophosphoryl-P-trichloromonophosphazene monomer;

[0058] S1.2: reacting N-dichlorophosphoryl-P-trichloromonophosphazene monomer in a nitrogen atmosphere at 240° C. for 2 h, and obtaining an intermediate product, polydichlorophosphazene;

[0059] S2: Preparation of new flame retardants

[0060] S2.1: 8 parts by weight of the intermediate product polydichlorophosphazene was dissolved in 230 parts by weight of tetrahydrofuran, and then 3 parts by weight of 4-hydroxysodium benzaldehyde was added, and the mixture was reacted at 65° C. and nitrogen atmosphere for 6 hours. After the reaction was completed, 3 parts by weight of sodium phenolate was added, and the mixture was reacted at 70° C. for 20 hours. After the reaction was completed, the mixture was filtered, washed, and dried to obtain reactant Ⅰ [(NP(OC6H4CHO)(OPh)) 0.4 (POPh2) 0.6 ] n ;

[0061] S2.2: Dissolve 5 parts by weight of reactant I in a mixed solution of 12 parts by weight of tetrahydrofuran / methanol in a volume ratio of 1:1, then add 3 parts by weight of sodium borohydride, react for 23 hours under a nitrogen atmosphere, wash with hot water and dry after the reaction to obtain reactant II [(NP(OC6H4CH2OH)(OPh)) 0.4 (POPh2) 0.6 ] n ;

[0062] S2.3: After mixing 3 parts by weight of epichlorohydrin and 5 parts by weight of reactant II, 0.2 parts by weight of catalyst hexadecyltrimethylammonium bromide was added under nitrogen atmosphere, stirred at 70°C for 2h, then 3 parts by weight of 40wt% sodium hydroxide solution was added, reacted at 85°C for 2h, and after the reaction, rotary evaporation, washing, filtering and drying were performed to obtain a novel flame retardant;

[0063] S3: Preparation of modified melamine formaldehyde

[0064] S3.1: 0.2 parts by weight of urotropine and 60 parts by weight of formaldehyde solution are stirred and mixed, and then 12 parts by weight of melamine powder are added, and the mixture is heated to 80° C. in a water bath for reaction for 1 hour, and then triethanolamine is added to adjust the pH value to 9.3 to obtain a melamine-formaldehyde prepolymer;

[0065] S3.2: adding the above melamine-formaldehyde prepolymer to 70 parts by weight of methanol, stirring and mixing for 1-2 hours to obtain modified melamine formaldehyde;

[0066] S4: Preparation of organic phase change energy storage composite materials

[0067] S4.1: 12 parts by weight of styrene-maleic anhydride copolymer was added to 230 parts by weight of deionized water, and the mixture was stirred at 50° C. for 20 minutes, and then a 10 wt % sodium hydroxide solution was added to adjust the pH value to 9, and the mixture was stirred for 1 hour, and then 2 parts by weight of a new flame retardant and 0.5 parts by weight of sodium dialkylbenzene sulfonate were added and mixed to obtain a reaction solution;

[0068] S4.2: Add 8 parts by weight of dodecanol to 25 parts by weight of the reaction solution, stir and mix at 500 r / min, then add 2 parts by weight of modified melamine formaldehyde, then stir and react at 70°C for 1 hour, then add 2 parts by weight of a mixed solution of 10wt% boron carbide and carbon nanotubes in a weight ratio of 1:1, react for 1 hour, wash and dry after the reaction is cooled to obtain an organic phase change energy storage composite material.

[0069] Example 3

[0070] A preparation process of a self-flame retardant organic phase change energy storage composite material, such as Figure 1 As shown, the following steps are included:

[0071] S1: Preparation of novel flame retardant intermediates

[0072] S1.1: 80 parts by weight of phosphorus pentachloride, 220 parts by weight of tetrachloroethane and 10 parts by weight of ammonium sulfate were mixed uniformly under nitrogen protection, and the temperature was raised to 150°C for reaction for 2 hours. After the reaction was completed, the mixture was filtered and rotary evaporated under reduced pressure to obtain the reaction product, N-dichlorophosphoryl-P-trichloromonophosphazene monomer;

[0073] S1.2: reacting N-dichlorophosphoryl-P-trichloromonophosphazene monomer in a nitrogen atmosphere at 250° C. for 3 h, and obtaining an intermediate product, polydichlorophosphazene;

[0074] S2: Preparation of new flame retardants

[0075] S2.1: 5 parts by weight of the intermediate product polydichlorophosphazene are dissolved in 200 parts by weight of tetrahydrofuran, and then 2 parts by weight of 4-hydroxysodium benzaldehyde are added, and the mixture is reacted at 68° C. in a nitrogen atmosphere for 7 hours. After the reaction is completed, 2 parts by weight of sodium phenolate are added, and the mixture is reacted at 75° C. for 24 hours. After the reaction is completed, the mixture is filtered, washed, and dried to obtain reactant Ⅰ [(NP(OC6H4CHO)(OPh)) 0.4 (POPh2) 0.6 ] n ;

[0076] S2.2: 3 parts by weight of reactant I was dissolved in 10 parts by weight of a mixed solution of tetrahydrofuran / methanol in a volume ratio of 1:1, and then 2 parts by weight of sodium borohydride was added. The mixture was reacted for 24 hours under a nitrogen atmosphere. After the reaction, it was washed with hot water and dried to obtain reactant II [(NP(OC6H4CH2OH)(OPh))0.4 (POPh2) 0.6 ] n ;

[0077] S2.3: After mixing 2 parts by weight of epichlorohydrin and 3 parts by weight of reactant II, 0.1 parts by weight of catalyst hexadecyltrimethylammonium bromide was added under nitrogen atmosphere, stirred at 75°C for 3 hours, then 2 parts by weight of 40wt% sodium hydroxide solution was added, reacted at 88°C for 3 hours, and after the reaction, rotary evaporation, washing, filtering and drying were performed to obtain a novel flame retardant;

[0078] S3: Preparation of modified melamine formaldehyde

[0079] S3.1: 0.1 parts by weight of hexamethylenetetramine and 50 parts by weight of formaldehyde solution are stirred and mixed, and then 10 parts by weight of melamine powder are added, and the mixture is heated to 85° C. in a water bath for reaction for 2 hours, and then triethanolamine is added to adjust the pH value to 9.1 to obtain a melamine-formaldehyde prepolymer;

[0080] S3.2: adding the above melamine-formaldehyde prepolymer to 60 parts by weight of methanol, stirring and mixing for 2 hours to obtain modified melamine formaldehyde;

[0081] S4: Preparation of organic phase change energy storage composites

[0082] S4.1: Add 10 parts by weight of styrene-maleic anhydride copolymer to 200 parts by weight of deionized water, stir and mix at 55° C. for 30 minutes, then add 10 wt% sodium hydroxide solution to adjust the pH value to 8, stir for 2 hours, then add 1 part by weight of a new flame retardant and 0.4 parts by weight of sodium dialkylbenzene sulfonate to obtain a reaction solution;

[0083] S4.2: Add 7 parts by weight of dodecanol to 23 parts by weight of the reaction solution, stir and mix at 600 r / min, then add 1 part by weight of modified melamine formaldehyde, then stir at 75°C for 2 hours, then add 1 part by weight of a mixed solution of 10wt% boron carbide and carbon nanotubes in a weight ratio of 1:1, react for 2 hours, wash and dry after the reaction is cooled to obtain an organic phase change energy storage composite material.

[0084] The thermal conductivity and latent heat of phase change of Examples 1-3 were measured. The measurement results are shown in Table 1.

[0085] Table 1. Thermal conductivity and latent heat of phase change of Examples 1-3

[0086] Thermal conductivity W / (m·k) Latent heat of phase change J / g Example 1 1.57 168.5 Example 2 1.53 167.3 Example 3 1.54 167.5

[0087] According to the data in Table 1, it can be seen that the organic phase change energy storage composite material prepared by the present invention has good thermal conductivity, can effectively transfer heat, and the organic phase change energy storage composite material can store and release considerable heat during the phase change process, and has good phase change energy storage capacity.

[0088] Comparative Example 1

[0089] Compared with Example 1, the difference of Comparative Example 1 is that, in Comparative Example 1, the novel flame retardant in steps S1-S2 and step S4.1 is removed, and the remaining steps remain unchanged to prepare the organic phase change energy storage composite material, which is recorded as Comparative Example 1.

[0090] The flame retardant properties of Examples 1-3 and Comparative Example 1 were measured, and the measurement results are shown in Table 2.

[0091] Table 2. Flame retardant properties of Examples 1-3 and Comparative Example 1

[0092]

[0093] It can be seen from the data in Table 2 that the organic phase change energy storage composite material prepared after adding the new energy flame retardant has good flame retardant properties.

[0094] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A preparation process of a self-flame retardant organic phase change energy storage composite material, characterized in that: The steps include: S1: Preparation of novel flame retardant intermediates Phosphorus pentachloride, tetrachloroethane and ammonium sulfate are used as raw materials to react to generate N-dichlorophosphoryl-P-trichloromonophosphazene monomer, which is then reacted again to prepare an intermediate product, polydichlorophosphazene; S2: Preparation of new flame retardants After multi-step synthesis, a variety of flame retardant functional groups were introduced to prepare a new flame retardant; S3: Preparation of modified melamine formaldehyde The melamine-formaldehyde prepolymer is modified by methanol to obtain modified melamine formaldehyde; S4: Preparation of organic phase change energy storage composite materials A reaction solution is prepared by mixing styrene-maleic anhydride copolymer, sodium hydroxide, a new flame retardant and sodium dialkylbenzene sulfonate, dodecanol is added to the reaction solution, and then modified melamine formaldehyde and a mixed solution of boron carbide and carbon nanotubes are added, mixed and reacted to obtain an organic phase change energy storage composite material.

2. The preparation process of a self-flame retardant organic phase change energy storage composite material according to claim 1, characterized in that: Step S1: Preparation of novel flame retardant intermediate product, specifically comprising the following steps: S1.1: 80-90 parts by weight of phosphorus pentachloride, 220-230 parts by weight of tetrachloroethane and 10-12 parts by weight of ammonium sulfate are mixed uniformly under nitrogen protection, and the temperature is raised to 145-150° C., and the reaction is carried out for 1-2 hours. After the reaction is completed, the reaction is filtered and the reaction is rotary evaporated under reduced pressure to obtain the reaction product, N-dichlorophosphoryl-P-trichloromonophosphazene monomer; S1.2: reacting N-dichlorophosphoryl-P-trichloromonophosphazene monomer in a nitrogen atmosphere at 240-250°C for 2-3h. After the reaction is completed, an intermediate product, polydichlorophosphazene, is obtained.

3. The preparation process of a self-flame retardant organic phase change energy storage composite material according to claim 2, characterized in that: Step S2: Preparation of the novel flame retardant, specifically comprising the following steps: S2.1: 5-8 parts by weight of the intermediate product polydichlorophosphazene is dissolved in 200-230 parts by weight of tetrahydrofuran, and then 2-3 parts by weight of 4-hydroxysodium benzaldehyde is added, and the mixture is reacted at 65-68° C. and nitrogen atmosphere for 6-7 hours. After the reaction is completed, 2-3 parts by weight of sodium phenolate are added, and the mixture is reacted at 70-75° C. for 20-24 hours. After the reaction is completed, the mixture is filtered, washed, and dried to obtain reactant Ⅰ [(NP(OC6H4CHO)(OPh)) 0.4 (POPh2) 0.6 ] n ; S2.2: 3-5 parts by weight of reactant I are dissolved in 10-12 parts by weight of a mixed solution of tetrahydrofuran / methanol, and then 2-3 parts by weight of sodium borohydride are added, and the mixture is reacted for 23-24 hours under a nitrogen atmosphere. After the reaction, the mixture is washed with hot water and dried to obtain reactant II [(NP(OC6H4CH2OH)(OPh)) 0.4 (POPh2) 0.6 ] n ; S2.3: After mixing 2-3 parts by weight of epichlorohydrin and 3-5 parts by weight of reactant II, add 0.1-0.2 parts by weight of catalyst hexadecyltrimethylammonium bromide under a nitrogen atmosphere, stir at 70-75°C for 2-3 hours, then add 2-3 parts by weight of sodium hydroxide solution, react at 85-88°C for 2-3 hours, and after the reaction, perform rotary evaporation, wash, filter and dry to obtain a new flame retardant.

4. The preparation process of a self-flame retardant organic phase change energy storage composite material according to claim 3, characterized in that: Step S3: Preparation of modified melamine formaldehyde, specifically comprising the following steps: S3.1: 0.1-0.2 parts by weight of hexamethylenetetramine and 50-60 parts by weight of formaldehyde solution are stirred and mixed, and then 10-12 parts by weight of melamine powder are added, and the mixture is heated in a water bath to 80-85° C. for reaction for 1-2 hours, and then triethanolamine is added to adjust the pH value to 9.1-9.3 to obtain a melamine-formaldehyde prepolymer; S3.2: Add the above melamine-formaldehyde prepolymer to 60-70 parts by weight of methanol, stir and react for 1-2 hours to obtain modified melamine formaldehyde.

5. The preparation process of a self-flame retardant organic phase change energy storage composite material according to claim 4, characterized in that: Step S4: Preparation of organic phase change energy storage composite material, specifically comprising the following steps: S4.1: Add 10-12 parts by weight of styrene-maleic anhydride copolymer to 200-230 parts by weight of deionized water, stir and mix at 50-55° C. for 20-30 minutes, then add sodium hydroxide solution to adjust the pH value to 8-9, stir for 1-2 hours, then add 1-2 parts by weight of a new flame retardant and 0.4-0.5 parts by weight of sodium dialkylbenzene sulfonate to obtain a reaction solution; S4.2: Add 7-8 parts by weight of dodecanol to 23-25 ​​parts by weight of the reaction solution, stir and mix at 500-600 r / min, then add 1-2 parts by weight of modified melamine formaldehyde, then stir and react at 70-75°C for 1-2 hours, then add 1-2 parts by weight of a mixed solution of 10wt% boron carbide and carbon nanotubes, react for 1-2 hours, wash and dry after the reaction is cooled to obtain an organic phase change energy storage composite material.

6. The preparation process of a self-flame retardant organic phase change energy storage composite material according to claim 3, characterized in that: The volume ratio of tetrahydrofuran to methanol in step S2.2 is 1:

1.

7. The process for preparing a self-flame retardant organic phase change energy storage composite material according to claim 3, characterized in that: The sodium hydroxide solution in step S2.3 is a 40 wt % sodium hydroxide solution.

8. The process for preparing a self-flame retardant organic phase change energy storage composite material according to claim 5, characterized in that: The sodium hydroxide solution in step S4.1 is a 10 wt % sodium hydroxide solution.

9. The process for preparing a self-flame retardant organic phase change energy storage composite material according to claim 5, characterized in that: The weight ratio of boron carbide to carbon nanotubes in the mixed solution of step S4.2 is 1:

1.

10. A self-flame retardant organic phase change energy storage composite material, characterized in that: The composite material is prepared by the preparation process of a self-flame retardant organic phase change energy storage composite material according to any one of claims 1 to 9.